Comparison between the PaxView TB/NTM MPCR-ULFA Kit and Xpert MTB/RIF for Mycobacterium Tuberculosis Detection in Indonesian Clinical Isolates - Ayunda Imaniar; Ucy Nadjmiyah; Munawaroh Fitriah; Soedarsono Soedarsono; Aryati Aryati (Indian Journal of Forensic Medicine & Toxicology, 2021)
The PaxView TB/NTM MPCR-ULFA Kit, which targets the IS6110 and mtp40 genes for Mycobacteriumtuberculosis (MTB) detection, is a novel tool that substitutes gel electrophoresis for universal lateral flowassays. The sensitivity and specificity of this method were compared with those of established methodologiesusing Indonesian clinical isolates. In this study, 317 sputum specimens isolated from tuberculosis (TB)suspects were examined to evaluate the performance of the PaxView TB/NTM MPCR-ULFA Kit comparedto that of smear microscopy and the Xpert MTB/RIF assay. Out of 317 cases, the rate of TB-positivesamples evaluated by different methods was 33.4% (106/317; 95% CI 28.2-38.6) for smear microscopy,37.9% (120/317; 95% CI 32.5-43.2) for the Xpert MTB/RIF, and 40.7% (129/317; 95% CI 35.3-46.1) forthe PaxView TB/NTM MPCR-ULFA Kit. Compared to the Xpert MTB/RIF as a standard reference, thePaxView TB/NTM MPCR-ULFA Kit was found to possess a 92.5% sensitivity (111/120; 95% CI 87.8-97.2), a 90.8% specificity (179/197; 95% CI 86.8-94.8), 86.0% PPV (111/129; 95% CI 80.0-92.0), anda NPV 95.2% (179/188; 95% CI 92.2-98.3). The PaxView TB/NTM MPCR-ULFA Kit could be a usefulmolecular diagnostic tool to identify MTB in clinical samples in resource-limited countries, as this procedureis more cost-effective and sensitive than the Xpert MTB/RIF, and more convenient than conventional PCRgel electrophoresis approaches.